Everyday mathematics: profit and loss, cost price and selling price - Khalid, Madihah; Hj Ismail, Zurimah (National Council of Teachers in Mathematics (NCTM), 2015)
This book is one of two designed to bring awareness to various international perspectives on mathematical topics taught throughout the world. Classroom activities herein showcase topics discussed at the International Congress on Mathematics Education (ICME-12) held in Seoul, South Korea, in July, 2012